Legal regulation of economic activity and economic relations in a special period - Прохоренко, Михайло Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Defense issues have gained a vital importance today for the Ukrainian people, as well as the protection of state sovereignty and territorial integrity. Since the anti-terrorist operations in Donetsk and Lugansk regions has been launched, the national economy, public authorities, other public bodies, local authorities, Armed Forces of Ukraine and other military units, civil defense forces, enterprises, institutions and organizations were shifted to special period of functioning. The existing significant legal array of economic activities during a special period requires theoretical and legal analysis for proper coordination of legislative norms by their regulatory subject and by their hierarchical structure in order to elaborate some suggestions to amend the existing economic legislation of Ukraine. Economic activity in times of crisis is a separate special mode of economic relations, carried out by public authorities, military command, the military administrations of other government agencies, local governments, enterprises, institutions and organizations during mobilization (except targeted one) in the period of martial law and / or wartime, and partly in the recovery period after the end of hostilities. The scope of economic relations in a particular period is represented by: 1) organizational and economic relations of public authorities, military command, law enforcement, military administration for the proper implementation and further application of a special period; 2) economic and industrial relations of the companies and organizations, performing direct economic activity taking into account regulatory forth restrictions on the rights and freedoms of the activity; 3) intraeconomic relations subject to the limitations of common standards during mobilization (except targeted one) in the period of martial law and / or of war, and partly in recovery period after the end of hostilities. Having considered the current imperfect state of economic activity regulation and economic relations in times of crisis, there were elaborated some practical recommendations, namely: 1) to adopt the Law of Ukraine "On legal regime of the recovery period." 2) to do amendments to Part. 1, Art. 417 of the Commercial Code of Ukraine of January 16, 2003 and put it as follows: "1. In times of crisis the legal mode of economic activity is based on the legislative acts aiming to protect the sovereignty, territorial integrity and inviolability of Ukraine, establishing and ensuring human rights and freedoms.